METHODS, MEANS AND TECHNOLOGIES OF INFORMATION PROTECTION ON THE INTERNET (Conferencea, 2021)
The data can be divided into two types: Personal information of an individual (surname, first name, patronymic, passport data (Russian and foreign), SNILS, TIN, license numbers, data of his car, phone number, residential address, full name of the next of kin and their data, etc.); Information of companies (legal entity: both commercial and state organizations). This includes information about the manager, employees, confidential data representing a trade secret (company turnover, bank accounts, a list of contractors - suppliers and buyers) and so on